2021
DOI: 10.3389/fphy.2021.670317
|View full text |Cite
|
Sign up to set email alerts
|

Simple Physical Interactions Yield Social Self-Organization in Honeybees

Abstract: Social insect colonies show all characteristics of complex adaptive systems (CAS). Their complex behavioral patterns arise from social interactions that are based on the individuals’ reactions to and interactions with environmental stimuli. We study here how social and environmental factors modulate and bias the collective thermotaxis of young honeybees. Therefore, we record their collective decision-making in a series of laboratory experiments and derived a mathematical model of the collective decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Similar networks of feedbacks than those highlighted in this paper have been described to be present in other social systems [22,73,74]. A body of works devoted to such social systems where positive feedbacks are in competition highlights the emergence of multistable patterns…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar networks of feedbacks than those highlighted in this paper have been described to be present in other social systems [22,73,74]. A body of works devoted to such social systems where positive feedbacks are in competition highlights the emergence of multistable patterns…”
Section: Discussionsupporting
confidence: 79%
“…Similar networks of feedbacks than those highlighted in this paper have been described to be present in other social systems [ 22 , 73 , 74 ]. A body of works devoted to such social systems where positive feedbacks are in competition highlights the emergence of multistable patterns of organization that depends on different elements such as the size of the system, the environmental parameters and the strength of the interactions/interattractions [ 58 , 75 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It was found that such complex processes can be modeled well by multi-agent models in a bottom-up way if the mechanisms of agents employ threshold-based behavior triggers and modulators. The simplest types of such models have fixed stimulus-threshold mechanisms, these models have been for example developed for modeling ants ( Bonabeau et al, 1996 , 1998 ), honeybees ( Schmickl et al, 2012 ; Szopek et al, 2021a ) and termites ( Feltell et al, 2008 ). Often, and also for our needs here, such fixed thresholds are not powerful enough to capture the observed dynamics in the system.…”
Section: Discussionmentioning
confidence: 99%